(untitled) - Smith, Alastair (a Cambridge, UK, 2004)
Most parliamentary systems have endogenous election timing, where the Prime Minister is free to call for elections when he or she thinks it's appropriate to do so. Despite the huge advantage one might expect this opportunity creates, Prime Ministers still lose frequently. Alastair Smith proposes an informational theory that relates the time when leaders call for elections to the consequences of their decisions. Smith demonstrates why leaders find it difficult to profit from their ability to call for elections, even when they are popular and face weak opposition.
Keywords: Elections,Bầu cử; Great Britain